Mechanical evaluation of recycled PETG filament for 3D printing - Vlad Dohan; Sergiu-Valentin Galatanu; Liviu Marsavina (Fracture and Structural Integrity)
Additive manufacturing (AM) is revolutionizing various industries by enabling the creation of complex structures with minimal waste. In the context of a circular economy, the importance of recycling cannot be overstated, as it plays a crucial role in reducing environmental impact and conserving resources. This study investigates the mechanical behavior of PETG in the context of recycling for 3D printing applications. With plastic waste posing significant environmental challenges, the pursuit of sustainable solutions is paramount. PETG has emerged as a promising material in additive manufacturing due to its favorable properties, but its sustainability remains a concern. Through mechanical testing, including tensile, compression, and impact tests, PETG specimens are evaluated after one cycle of recycling and reutilization